Residential Building Varieties in the Bukhara Oasis - Yunusov Sh. M. (Researchparks Publishing, 2022)
The article discusses the main features in the differences between the settlements in the Bukhara oasis. Based on inter-district climate change and land salinity levels, prefabricated houses were analyzed. There are ideas to build the same housing in all corners of the territory of the Republic of Uzbekistan